The Relationship between Knee Functional Disability and Sleep Quality in Genitourinary Osteoarthritis Patients: A Systematic Literature Review - Alif Rizq Mugeni; Bernadeth Novita (International Journal Of Health Science, 2026)
Knee osteoarthritis is a leading cause of chronic pain and functional disability, particularly among adults and the elderly, and is often accompanied by sleep disturbances. The functional disability of the knee and sleep quality are interrelated, contributing to a decline in patients’ quality of life. This systematic literature review aims to examine the relationship between knee functional disability and sleep quality in patients with knee osteoarthritis, evaluating the consistency and strength of this connection based on recent studies. Following PRISMA guidelines, a search of the Scopus, PubMed, Google Scholar, SpringerLink, and ScienceDirect databases was conducted for articles published from 2021 to 2025. Inclusion criteria encompassed studies on knee osteoarthritis patients, addressing knee functional disability and sleep quality through cross-sectional, cohort, or quasi-experimental designs. Ten articles met the inclusion criteria and were analyzed using a descriptive-narrative approach. Results showed a significant association between knee functional disability and poor sleep quality, with pain, stiffness, and activity limitations identified as key contributors. Many studies reported a bidirectional relationship, where sleep disturbances increased pain and worsened functional limitations. About 60% of studies highlighted sleep quality as a predictor of functional decline and knee osteoarthritis progression. These findings emphasize the importance of a rehabilitation approach that includes improving sleep quality to manage knee osteoarthritis effectively.